2018
DOI: 10.14814/phy2.13855
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal rhythms of heart and respiratory rates in donkeys of different age groups during the cold-dry and hot-dry seasons in a tropical savannah

Abstract: The aim of this study was to determine the effect of season on diurnal rhythms of heart (HR) and respiratory rates (RespR) in the adult, yearling, and foal donkeys during the cold‐dry and hot‐dry seasons under natural light/dark cycle. The resting HR and RespR were recorded bihourly for 24 consecutive hours from 06:00 to 06:00 h (GMT +1) in 30, clinically healthy donkeys (10 adults,10 yearlings, and 10 foals). Dry‐bulb temperature (DBT), relative humidity (RH), temperature‐humidity index (THI) and wet‐bulb glo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 56 publications
1
4
2
Order By: Relevance
“…The result in packing (with melatonin) donkeys was similar to the report of Zakari et al (2018b) , who reported that the peak RR occurred at 14:10 ± 0.2 h in yearling donkeys during the hot-dry season, while the acrophase obtained in packing (without melatonin) was significantly higher. This observation may be due to the effect of packing and the antioxidant effect of melatonin in the donkeys that were administered melatonin and subjected to packing.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The result in packing (with melatonin) donkeys was similar to the report of Zakari et al (2018b) , who reported that the peak RR occurred at 14:10 ± 0.2 h in yearling donkeys during the hot-dry season, while the acrophase obtained in packing (without melatonin) was significantly higher. This observation may be due to the effect of packing and the antioxidant effect of melatonin in the donkeys that were administered melatonin and subjected to packing.…”
Section: Discussionsupporting
confidence: 88%
“…Body temperature has direct influence on the value of RR ( Mortola, 2004 ) and melatonin has been reported to have capacity to reduce body temperature ( Cagnacci, 1996 ; Depres-Brummer et al, 1998 ; Atkinson et al, 2005 ; Simko et al, 2016 ), thereby indirectly influencing the rhythm of RR. The mesor of RR obtained in the current study was higher compared to the value obtained by Zakari et al (2018b) in donkeys that were not subjected to packing. The difference in the observations may be due to the impact of packing on the donkeys.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…Measurements of basic physiological parameters are easy to access and are used as the first indicators of the well-being of working donkeys. The HR of an animal is one of the physiological parameters measured to determine its health status or response to activities with increased energy demands, like packing [ 2 , 25 ]. In order to ensure more humane handling of the donkey, there is need to obtain information that will maximise their potential use in packing and be beneficial in establishing guidelines for their humane handling for packing purposes in different seasons of the year.…”
Section: Introductionmentioning
confidence: 99%
“…The RR and HR of donkeys have been reported to increase after packing exercise [ 13 , 19 ]. The daily rhythmicity of RR and HR has been reported in donkeys during the hot-dry season [ 25 ]. However, the effects of different workloads on the daily rhythmicity of RR and HR during the hot-dry season have not been investigated.…”
Section: Introductionmentioning
confidence: 99%